Why Does Anemia Lead to Chronic Heart Failure? - Mamajonova Muslima Umidjon qizi (Scholars Digest Publishing, 2023)
Epidemiological study indicates the impact of anemia in the pathogenesis, prognosis and complications of cardiovascular diseases. In the last decade, the possibilities of treating anemia in patients with CHF have been studied actively. The research was carried out in 120 patients with chronic heart disease in cardiology department of multidisciplinary clinic of Tashkent medical academy. Results showed that over 90% percent of patients were suffering from anemia which was increasing the risk of death from heart failure.
Keywords: Anemia, heart failure, iron deficiency, cardiorenal syndrome.